2021
DOI: 10.1109/access.2021.3063295
|View full text |Cite
|
Sign up to set email alerts
|

Anchor Nodes Assisted Cluster-Based Routing Protocol for Reliable Data Transfer in Underwater Wireless Sensor Networks

Abstract: Reliable data transfer seems a quite challenging task in Underwater Wireless Sensor Networks (UWSN) in comparison with Terrestrial Wireless Sensor Networks due to the peculiar attributes of UWSN communication. However, the reliable data transmission in UWSN is very limited. Yet, there is a way to achieve reliable data transfer metrics through the design of routing protocols by considering the exceptional features of UWSN communications. With this aim, we propose two schemes with multiple sinks-based network ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Our results match accurately those of Light-Sync about the synchronization accuracy, regardless of the number of nodes in the UWSN. The importance of validating synchronization algorithms by means of simulation is clearly important, as also shown in [7].…”
Section: Resultsmentioning
confidence: 99%
“…Our results match accurately those of Light-Sync about the synchronization accuracy, regardless of the number of nodes in the UWSN. The importance of validating synchronization algorithms by means of simulation is clearly important, as also shown in [7].…”
Section: Resultsmentioning
confidence: 99%
“…Karim et al [19] suggested two network frameworks with numerous sinks: the VH-ANCRP technique for addressing local maximum nodes and the ANCRP approach for obtaining consistent data transmission metrics. To form clusters, the network areas are divided into smaller cubes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sarang et al 14 have proposed two plans with numerous sinks‐based organization designs: Anchor nodes helped cluster‐based routing protocol (ANCRP) to accomplish solid information move measurements and Void Handling method in ANCRP (VH‐ANCRP) to adapt to the nearby greatest hubs. For which, the organization space is partitioned into little 3D shapes to frame bunches.…”
Section: Review Of Related Literaturementioning
confidence: 99%